2016
DOI: 10.1523/jneurosci.3012-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Commissural Gain Control Enhances the Midbrain Representation of Sound Location

Abstract: Accurate localization of sound sources is essential for survival behavior in many species. The inferior colliculi (ICs) are the first point in the auditory pathway where cues used to locate sounds, ie, interaural time differences (ITDs), interaural level differences (ILDs), and pinna spectral cues, are all represented in the same location. These cues are first extracted separately on each side of the midline in brainstem nuclei that project to the ICs. Because of this segregation, each IC predominantly represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 69 publications
2
21
0
1
Order By: Relevance
“…The activation of NMDA receptors in our recordings may indicate that excitatory commissural synapses tend to be located on the distal dendrites or dendritic spines of VIP neurons, where the local membrane potential might be sufficiently depolarized by activation of AMPA receptors to remove Mg 2+ block of NMDA receptors. A distal location would be consistent with the proposed modulatory role for commissural inputs (Orton et al, 2016; Orton and Rees, 2014). Similarly, the lack of NMDA receptor activation by DCN afferents might indicate that DCN synapses are located on proximal dendrites or possibly on the soma itself, or that these synapses lack NMDA receptors.…”
Section: Discussionsupporting
confidence: 77%
“…The activation of NMDA receptors in our recordings may indicate that excitatory commissural synapses tend to be located on the distal dendrites or dendritic spines of VIP neurons, where the local membrane potential might be sufficiently depolarized by activation of AMPA receptors to remove Mg 2+ block of NMDA receptors. A distal location would be consistent with the proposed modulatory role for commissural inputs (Orton et al, 2016; Orton and Rees, 2014). Similarly, the lack of NMDA receptor activation by DCN afferents might indicate that DCN synapses are located on proximal dendrites or possibly on the soma itself, or that these synapses lack NMDA receptors.…”
Section: Discussionsupporting
confidence: 77%
“…In this context, this study may invoke a similar mechanism of excitatory signal integration from the LL‐ and CoIC pathways at CNIC neurons. It has been recently shown that commissural inputs in the IC enhance sound localization in vivo (Orton, Papasavvas, & Rees, ), and present findings may have some functional relevance in the context of sound localization.…”
Section: Discussionsupporting
confidence: 68%
“…The 410 activation of NMDA receptors in our recordings may indicate that excitatory commissural synapses tend 411 to be located on the distal dendrites or dendritic spines of VIP neurons, where the local membrane 412 potential might be sufficiently depolarized by activation of AMPA receptors to remove Mg 2+ block of 413 NMDA receptors. A distal location would be consistent with the proposed modulatory role for 414 commissural inputs(Orton et al, 2016;Orton and Rees, 2014). Similarly, the lack of NMDA receptor 415 activation by DCN afferents might indicate that DCN synapses are located proximal to the soma, possibly 416 on the soma itself, or that these synapses lack NMDA receptors.…”
mentioning
confidence: 68%